Research on MIMU/BD integrated navigation with three-axis magnetometer aided - Chunni Feng; Xiaoping Hu; Xiaofeng He; Bing Luo; Jingyu Zhang; Hao Zhang (Proceedings of 2014 IEEE Chinese Guidance, Navigation and Control Conference, 2014)
Integration is a current trend in navigation system research. MIMU (Micro Inertial Measurement Unit) is compact, cheap, low-power, and highly reliable. BD (BeiDou System) is a satellite navigation system with our own independent intellectual property right. Integrating MIMU with BD can lessen MIMU's error accumulation and BD's low robustness, thus making MIMU/BD an ideal integrated navigation system. However, MIMU/BD has poor heading error observability. A three-axis magnetometer (TAM) can measure earth's magnetic field to obtain carrier heading. This paper focuses on improving heading accuracy of MIMU/BD integrated navigation system with TAM aided. TAMs are used to calculate the heading angle. Calibrating TAMs using a RLS algorithm with a forgetting factor is introduced. An integrated navigation algorithm based on Kalman Filter is used. Vehicle experiments show that this method efficiently improves the heading accuracy.